2022
DOI: 10.5114/pq.2022.121150
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic: regular physical activity and respiratory exercises at home as prevention and treatment

Abstract: The main question in the field of exercise and rehabilitation medicine is whether physical activity and therapeutic exercise are suitable activities for CoVid-19 patients who are recovering at home. There have been few public health guidelines provided about what people can do in relationship with exercise and respiratory care. For this reason, it is necessary that physical therapists give some recommendations concerning safe respiratory and physical exercises that could be executed by people with confirmed, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In addition to mental health disturbances, many research studies reported that, due to homeschooling and remote working during this time, feelings of fatigue, headache, and discomfort increased among university students. All of these situations resulted in low student motivation and task engagement, and low acceptance of online learning during the pandemic, which could have directly affected their academic performance [3,5,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to mental health disturbances, many research studies reported that, due to homeschooling and remote working during this time, feelings of fatigue, headache, and discomfort increased among university students. All of these situations resulted in low student motivation and task engagement, and low acceptance of online learning during the pandemic, which could have directly affected their academic performance [3,5,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%